2014
DOI: 10.7314/apjcp.2014.15.10.4187
|View full text |Cite
|
Sign up to set email alerts
|

Association of Matrix Metalloproteinase (MMP)-2 and -9 Expression with Extra-gastrointestinal Stromal Tumor Metastasis

Abstract: Matrix metalloproteinase (MMP)-2 and MMP-9 are important proteases involved in invasion and metastasis of various tumors. Extra-gastrointestinal stromal tumors (EGISTs) are rare neoplasms. This study was performed to assess MMP-2 and MMP-9 expression in EGIST tissue samples for association with clinicopathological data from the patients. Twenty-one surgical EGIST tissue specimens were collected for analysis of MMP-2 and MMP-9 expression using immunohistochemistry. MMP-2 and MMP-9 proteins were expressed in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…The expression and activity of MMPs against matrix macromolecules have been associated with the development of malignant phenotypes and the promotion of cell invasiveness and metastasis. MMP-2 and MMP-9 were two major MMPs mediating the degradation of the ECM (Wang et al, 2014). In our study, PPSS treatment not only reduced the protein expression but also suppressed the enzymatic activity of MMP-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 59%
“…The expression and activity of MMPs against matrix macromolecules have been associated with the development of malignant phenotypes and the promotion of cell invasiveness and metastasis. MMP-2 and MMP-9 were two major MMPs mediating the degradation of the ECM (Wang et al, 2014). In our study, PPSS treatment not only reduced the protein expression but also suppressed the enzymatic activity of MMP-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 59%
“…Matrix metalloproteinases (MMPs), which are molecules that are implicated in metastasis by various malignant tumors, have been investigated for their role in contributing to the ability of EGISTs to metastasize. A recent study demonstrated that increased MMP-2 and MMP-9 expression was associated with increased risk of metastasis and aggressive behavior in E-GISTs (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The role of MMPs in tumor metastasis mainly includes: 1) Destructing local tissue structure and promoting tumor growth; 2) destructing the basement membrane barrier, which facilitates tumor metastasis; 3) promoting tumor neovascularization by improving the ECM. The degradation of ECM mainly depends on proteolytic enzymes; MMPs are an extremely important type of proteolytic enzyme (42,43). MMPs are Zn 2+ -and Ca 2+ -dependent proteases that may be classified by four types according to specific substrates: 1) Collagenase (MMP-1, -8 and -13); 2) gelatinase (MMP-2 and -9); 3) stromelysin (MMP-3, -7, -10 and -11); 4) Membrane type metal protein enzymes (MMP-14, -15, -16 and -17) (44,45).…”
Section: Discussionmentioning
confidence: 99%